SalonOvations' braids & updo's made easy - Jamie Rines Jones (Milady Pub., 1996)
You've recently purchased Cubase. You're ready to set up your home recording studio and finally produce that album you've been talking about. Now what? Your Cubase Studio provides a complete guide to setting up your digital recording studio with Cubase so you can start recording music right away. It starts with a general introduction to Cubase and digital recording, optimizing your computer to get the best sound, purchasing the right equipment that suits your budget, and the basics of acoustics. It then moves on to provide a complete overview of the recording process, whether you're laying down the perfect vocal, guitar, and bass tracks simultaneously or separately, and how to use MIDI most effectively.